2010
DOI: 10.1097/pas.0b013e3181cd3aeb
|View full text |Cite
|
Sign up to set email alerts
|

B-cell Lymphomas With Concurrent IGH-BCL2 and MYC Rearrangements Are Aggressive Neoplasms With Clinical and Pathologic Features Distinct From Burkitt Lymphoma and Diffuse Large B-cell Lymphoma

Abstract: B-cell lymphomas with concurrent IGH-BCL2 and MYC rearrangements, also known as “double-hit” lymphomas (DHL), are rare neoplasms characterized by highly aggressive clinical behavior, complex karyotypes, and a spectrum of pathological features overlapping with Burkitt lymphoma (BL), diffuse large B-cell lymphoma (DLBCL) and B-lymphoblastic lymphoma/leukemia (B-LBL). The clinical and pathological spectrum of this rare entity, including comparison to other high-grade B-cell neoplasms, has not been well defined. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

24
289
4
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 322 publications
(322 citation statements)
references
References 49 publications
24
289
4
5
Order By: Relevance
“…Snuderl et al [54] confirm by studying 20 cases that these aggressive neoplasms are distinct from DLBL and BL.…”
Section: New Entities/subtypessupporting
confidence: 62%
“…Snuderl et al [54] confirm by studying 20 cases that these aggressive neoplasms are distinct from DLBL and BL.…”
Section: New Entities/subtypessupporting
confidence: 62%
“…In the 20 cases of MYC/BCL2 double-hit lymphoma reported by Snuderl et al, 15 one patient had MYC rearrangement with extra copies of BCL2 and had a poor prognosis. Jiang et al 38 studied 60 cases of DLBCL and identified 18 cases with BCL2 gene amplification.…”
Section: Discussionmentioning
confidence: 92%
“…[4][5][6][7][8][9][10][11][12][13][14] Numerous case series of MYC/BCL2 double-hit lymphoma are reported in the literature. [15][16][17][18][19][20][21][22][23][24] MYC/ BCL2 DHLs represent B10% of all lymphomas that otherwise resemble diffuse large B-cell lymphoma (DLBCL). 10 Although different studies have focused on different aspects or details of double-hit lymphoma, all studies suggest that patients with these lymphomas commonly have an aggressive clinical course characterized by advanced stage disease, extranodal involvement, and high serum lactate dehydrogenase levels.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 In particular, the so-called 'double-hit' lymphomas that are characterized by MYC rearrangement and a concurrent rearrangement of other B-cell lymphomaassociated genes such as BCL2 or BCL6 are associated with poor response to therapy, aggressive clinical course and dismal prognosis. [5][6][7] These lymphomas are classified as 'B-cell lymphoma, unclassifiable with features intermediate between diffuse large B-cell lymphoma and Burkitt lymphoma' in the current 2008 WHO classification of hematopoietic neoplasms. 8 Evaluation for MYC alterations in diffuse large B-cell lymphoma is typically performed by fluorescence in situ hybridization (FISH).…”
mentioning
confidence: 99%